2002
DOI: 10.1029/2001jb000170
|View full text |Cite
|
Sign up to set email alerts
|

Seismic velocity and attenuation structures in the top of the Earth's inner core

Abstract: We collect a global data set of PKIKP and PKiKP phases recorded by the Global Seismic Network and many regional seismic arrays to study seismic structure in the top of the Earth's inner core. The PKIKP and PKiKP observations show different characteristics between those sampling the “eastern” hemisphere (40°E–180°E) of the inner core and those sampling the “western” hemisphere (180°W–40°E). PKIKP phases (1) arrive about 0.4 s earlier than the theoretical arrivals based on Preliminary Reference Earth Model (PREM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
140
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(163 citation statements)
references
References 43 publications
19
140
4
Order By: Relevance
“…5, left column). All this is different from the observed east-west dichotomy from the PKPbc-df data set, according to which the quasi-eastern hemisphere is faster than the quasiwestern hemisphere (Tanaka & Hamaguchi 1997;Wen & Niu 2002). This likely confirms that the effects from the lowermost mantle are too strong for our assumption to be valid, i.e.…”
Section: Application To Global Data Sets Sensitive To the Lowermost Mcontrasting
confidence: 40%
“…5, left column). All this is different from the observed east-west dichotomy from the PKPbc-df data set, according to which the quasi-eastern hemisphere is faster than the quasiwestern hemisphere (Tanaka & Hamaguchi 1997;Wen & Niu 2002). This likely confirms that the effects from the lowermost mantle are too strong for our assumption to be valid, i.e.…”
Section: Application To Global Data Sets Sensitive To the Lowermost Mcontrasting
confidence: 40%
“…6C) and the 10-km wavelength of the topography, our observations are in agreement with an eastward rotation of the inner core with respect to the mantle at a rate of Ϸ0.12-0.15°per year (see Materials and Methods), compatible with scattered-wave-and normal-mode-based estimates (11,21). The viscosity at the top of the inner core would have to be large enough to sustain such topography over a time scale of decades (4), or it could be sustained by small-scale convection in the top layers of the inner core (22). (Fig.…”
Section: Data Results and Discussionmentioning
confidence: 88%
“…The relative amplitude differences between PKP precursors and PKIKP are also affected by inner core attenuation (Wen and Niu, 2002;Waszek et al, 2015) or topography at the CMB (Doornbos, 1978;Bataille and Flatté, 1988). To test the inner core effect, we checked PKIKP turning points of the earthquakes in the three sub-regions, and found that they were highly random and intermixed with each other.…”
Section: Origin Of the Scatterersmentioning
confidence: 99%